The Prevalence of Hepatitis E Virus Infection in the Adult Turkish Population: A Systematic Review of the Literature and Prevalence Study in Blood Donors in Mersin Province - Sezgin, Orhan; Yaraş, Serkan; Ülger, Seda Tezcan; Aslan, Gönül; Tiftik, Eyyüp Naci (Turkish Journal of Gastroenterology, 2021)
Background: The hepatitis E virus (HEV) is an RNA virus that causes acute hepatitis, and can become chronic in immunocompromisedpatients, though this is rare. The frequency of HEV infection varies, depending on factors such as geographical region, socioeconomiclevel, and age. Despite limited studies on the adult population in Turkey, there is no current information about HEV frequency in ourcountry. Therefore, we aimed to scrutinize the data found from such studies, in comparison to our own results.Methods: A total of 900 volunteers who applied to donate blood to the University Hospital Blood Center and accepted the use of theirdata were enrolled in the study. Serum anti-HEV IgG antibody (Ab) was examined by the enzyme-linked immunosorbent assays method.The donors’ location, occupation, and animal contact status were determined. In addition, we evaluated the full text and conferencepapers (in Turkish or English) of Turkey-based HEV seroprevalence studies from 1990-2020, investigating the adult population.Results: The average age of the 900 volunteers in the study was 35.22 ± 9.60 years, of whom 889 (98.7%) were men. Anti-HEV IgG waspositive in 12.8% of the serum samples. The average age of the volunteers who were seropositive was 40.40 ± 9.72 years, and 98.2%were men. No association was found between anti-HEV IgG positivity and occupation, place of residence, and contact with animals. Anevaluation of the studies conducted in Turkey reveals that the average HEV infection seroprevalence is 9.52% in the healthy population,and the prevalence is increased in the region of Southeastern Anatolia. Patients with acute hepatitis and hemodialysis also hadincreased rates.Conclusion: The anti-HEV IgG seropositivity rate in healthy blood donors in Mersin province was 12.8%, and was similar to the ratesreported earlier in our country. However, this rate, found in a sample of individuals from a healthy society, causes concern about whatthe frequency may be in sick people. Wide-ranging community screening is needed.